EFEKTIVITAS INFUSA DAUN UBI JALAR (Ipomea batatas L) TERHADAP PENINGKATAN TROMBOSIT PADA MENCIT (Mus musculus) - Khaerani Khaerani; Hasyim Barium; Faridah Yenny Nonci (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Dengue fever is a disease that is still worrying for the people of Indonesia. Purple potato in general are well known in the community. Purple potato can be grown in all parts of Indonesia. Nutrient content of owned potatoes are very abundant, such as carbohydrates, proteins, vitamins, carotenoids  and  anthocyanin pigments  β-  needed  by the  body and  can  act  as  a  source  of antioxidants that can improve of platelets in thrombocytopenia condition. Research with an experimental design examined the effects of infusion of potato leaves in mice compared with various doses. And the results obtained in the form of an increase in platelet counts significantly in the provision of 200 g / 500 mL of achieving an increase in 203 / mm3 within 7 days.